Health Care Providers as Agents of Change: Integrating PrEP With Other Sexual and Reproductive Health Services for Adolescent Girls and Young Women - O'Malley, Gabrielle; Beima-Sofie, Kristin M.; Roche, Stephanie D.; Rousseau, Elzette; Travill, Danielle; Omollo, Victor; Delany-Moretlwe, Sinead; Bekker, Linda-Gail; Bukusi, Elizabeth A.; Kinuthia, John; Barnabee, Gena; Dettinger, Julie C.; et al. (Frontiers in Reproductive Health, 2021)
Background: Successful integration of pre-exposure prophylaxis (PrEP) with existing reproductive health services will require iterative learning and adaptation. The interaction between the problem-solving required to implement new interventions and health worker motivation has been well-described in the public health literature. This study describes structural and motivational challenges faced by health care providers delivering PrEP to adolescent girls and young women (AGYW) alongside other SRH services, and the strategies used to overcome them. Methods: We conducted in-depth interviews (IDIs) and focus group discussions (FGDs) with HCWs from two demonstration projects delivering PrEP to AGYW alongside other SRH services. The Prevention Options for the Women Evaluation Research (POWER) is an open label PrEP study with a focus on learning about PrEP delivery in Kenyan and South African family planning, youth mobile services, and public clinics at six facilities. PrIYA focused on PrEP delivery to AGYW via maternal and child health (MCH) and family planning (FP) clinics in Kenya across 37 facilities. IDIs and FGDs were transcribed verbatim and analyzed using a combination of inductive and deductive methods. Results: We conducted IDIs with 36 participants and 8 FGDs with 50 participants. HCW described a dynamic process of operationalizing PrEP delivery to better respond to patient needs, including modifying patient flow, pill packaging and counselling. HCWs believed the biggest challenge to sustained integration and scaling of PrEP for AGYW would be lack of health care worker motivation, primarily due to a misalignment of personal and professional values and expectations. HCWs frequently described concerns of PrEP provision being seen as condoning or promoting unprotected sex among young unmarried, sexually active women. Persuasive techniques used to overcome these reservations included emphasizing the social realities of HIV risk, health care worker professional identities, and vocational commitments to keeping young women healthy. Conclusion: Sustained scale-up of PrEP will require HCWs to value and prioritize its incorporation into daily practice. As with the provision of other SRH services, HCWs may have moral reservations about providing PrEP to AGYW. Strategies that strengthen alignment of HCW personal values with professional goals will be important for strengthening motivation to overcome delivery challenges.